The lethal giant larvae gene in Tribolium castaneum: molecular properties and roles in larval and pupal development as revealed by RNA interference - Xiao, Da; Liang, Xiao; Gao, Xiwu; Yao, Jianxiu; Zhu, Kun Yan (My University, 2014)
We identified and characterized the TcLgl gene putatively encoding lethal giant larvae (Lgl) protein from the red flour beetle (Tribolium castaneum). Analyses of developmental stage and tissue-specific expression patterns revealed that TcLgl was constitutively expressed. To examine the role of TcLgl in insect development, RNA interference was performed in early (1-day) larvae, late (20-day) larvae, and early (1-day) pupae. The early larvae injected with double-stranded RNA of TcLgl (dsTcLgl) at 100, 200, and 400 ng/larva failed to pupate, and 100% mortality was achieved within 20 days after the injection or before the pupation. The late larvae injected with dsTcLgl at these doses reduced the pupation rates to only 50.3%, 36.0%, and 18.2%, respectively. The un-pupated larvae gradually died after one week, and visually unaffected pupae failed to emerge into adults and died during the pupal stage. Similarly, when early pupae were injected with dsTcLgl at these doses, the normal eclosion rates were reduced to only 22.5%, 18.0%, and 11.2%, respectively, on day 7 after the injection, and all the adults with abnormal eclosion died in two days after the eclosion. These results indicate that TcLgl plays an essential role in insect development, especially during their metamorphosis.
Keywords: Eclosion; Lethal giant larvae (Lgl); Pupation; RNA interference; Tribolium castaneum